2019
DOI: 10.1016/j.jveb.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Zylkéne to load? The effects of alpha-casozepine on compliance and coping in horses during loading

Abstract: 1Horses are routinely travelled for access to safe off-road riding, veterinary care, 2 breeding, sale or moving to a new home environment. However, transport is a known 3 stressor in horses. For this reason, problem behaviour when loading is a commonly 4 reported issue which presents risks to handlers and horse welfare. Existing literature 5 and manufacturers recommendations suggests that alpha-casozepine may be 6 effective in improving the behaviour and welfare of horses during loading onto a 7 vehicle for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Ijichi et al 14 yielded similar results to this study. The effects of α-casozepine on compliance and coping in horses during loading was observed.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Ijichi et al 14 yielded similar results to this study. The effects of α-casozepine on compliance and coping in horses during loading was observed.…”
Section: Discussionsupporting
confidence: 90%
“…Horses weighing up to 500 kg were fed 1,000 mg, while horses over 500 kg were given 2,000 mg of Zylkene Equine. 14 It was observed that, at the dosage used, Zylkene had no effect on a horse's ability to cope with loading and confinement. 14 Further studies could examine the effectiveness of different dosages of Zylkene.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There are several supplements (e.g. tryptophan, alpha‐casozepine) that have been suggested to reduce anxiety and preloading stress, but the findings are conflicting (Burk and Williams, 2008; Ijichi et al., 2019). Horses showing TRPBs should not be loaded and should undergo a retraining programme (York et al., 2017).…”
Section: Assessmentmentioning
confidence: 99%
“…Saliva samples were taken with an Equisal swab gently moved over the tongue and lips of the subject (Ijichi et al, 2019 Vantaa, Finland). The results were calculated using four-parameter-logistic as recommended by the manufacturer.…”
Section: Salivary Cortisolmentioning
confidence: 99%